New perspectives in improving prognosis after myocardial infarction - N. M. Akhmedzhanov (Кардиоваскулярная терапия и профилактика)
The results of large, epidemiologic studies and clinical trials, e.g., GISSI-Prevenzione, demonstrate that highly purified omega-3 polyunsaturated fatty acids should be included into secondary prevention among myocardial infarction patients. Their positive clinical effects include: all-cause mortality reduction by 21%, mostly due to sudden death risk reduction by 45%.